2021
DOI: 10.1093/fampra/cmab114
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ views of pharmacist services in general practice: a qualitative evidence synthesis

Abstract: Background Pharmacist services in general practice are expanding worldwide, with evidence to show pharmacists’ presence in general practice has financial, workload, and clinical benefits. Yet, little is known globally about general practitioners’ (GPs’) views on their presence in general practice. Objective To synthesize the qualitative research evidence on GPs’ views of pharmacist services in general practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
0
21
1
1
Order By: Relevance
“…Whilst this study, like the recent QES, 11 found that some GPs were interested in pharmacists undergoing additional postgraduate training, a notable suggestion from the present study was to have internships in practices during pharmacists’ undergraduate training. Hazen et al designed a learning programme to train pharmacists to work in practices, and concluded that additional training is required to encourage role implementation.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…Whilst this study, like the recent QES, 11 found that some GPs were interested in pharmacists undergoing additional postgraduate training, a notable suggestion from the present study was to have internships in practices during pharmacists’ undergraduate training. Hazen et al designed a learning programme to train pharmacists to work in practices, and concluded that additional training is required to encourage role implementation.…”
Section: Discussioncontrasting
confidence: 43%
“…This study’s findings share broad similarity with the recent QES regarding GPs’ views on pharmacists in practices. 11 However, a notable contrast was that the present study had conflicting viewpoints about pharmacist capabilities in managing complex patients, e.g. whereby GPs included multimorbid older patients here.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In this study, it was apparent that the PBP role varied between practices and there were several activities undertaken by PBPs which have previously been identified. 12,24,26,[32][33][34][35][36][37][38][39][40][41] However, insufficient time and current workload were perceived as barriers to undertaking some activities and have been noted in other research. 23,35,39,40 Integrating pharmacy technicians into general practice was suggested as a way to save PBP time to conduct more clinical work and thus make better use of PBP skills.…”
Section: Comparison With Existing Literaturementioning
confidence: 96%